Flavonoids as Natural Anti-Inflammatory Agents Targeting Nuclear Factor-Kappa B (NFκB) Signaling in Cardiovascular Diseases: A Mini Review - Choy, Ker Woon; Murugan, Dharmani; Leong, Xin-Fang; Abas, Razif; Alias, Aspalilah; Mustafa, Mohd Rais (Frontiers in Pharmacology, 2019)
Cardiovascular diseases (CVDs) such as angina, hypertension, myocardial ischaemia and heart failure are the leading causes of morbidity and mortality worldwide. One of the major transcription factors widely associated with CVDs is nuclear factor-kappa B (NFκB). NFκB activation initiate the canonical and non-conical pathways that promotes activation of transcription factors leading to inflammation, such as leukocyte adhesion molecules, cytokines, and chemokines. Flavonoids are bioactive polyphenolic compounds found abundantly in various fruits, vegetables, beverages (tea, coffee), nuts and cereal products with cardiovascular protective properties. Flavonoids can be classified into six subgroups based on their chemical structures: flavanones, flavones, flavonols, flavan-3-ols, isoflavones and anthocyanidins. As NFκB inhibitors, these flavonoids may modulate the expression of pro-inflammatory genes leading to the attenuation of the inflammatory responses underlying various cardiovascular pathology. This review presents an update on the anti-inflammatory actions of flavonoids via inhibition of NFκB mechanism supporting the therapeutic potential of these natural compounds in various CVDs.